Increased Glomerular Hydrostatic Pressure is Associated with Tubular Creatinine Reabsorption in Healthy Subjects - Akihiro Tsuda; Eiji Ishimura; Yuri Machiba; Hideki Uedono; Shinya Nakatani; Katsuhito Mori; Junji Uchida; Masanori Emoto (Kidney & Blood Pressure Research, 2020)
Background: Cr is secreted by the proximal tubules and thus Cr clearance (Ccr) can overestimate inulin clearance (Cin). However, in some cases, Ccr can even underestimate Cin. This suggests that Cr could be reabsorbed in the tubuli. We examined the clinical parameters that are associated with tubular Cr reabsorption. Methods: In 80 kidney donor candidates (53.9 ± 13.2 years, 29 males), Cin and para-aminohippuric acid clearance were measured simultaneously. Intrarenal hemodynamic parameters were calculated by Gomez’s formulae. To quantify the secretory component of Ccr (SFcr), it was calculated as follows: SFcr = (Ccr − Cin)/Ccr. Results: Twenty-five subjects (31.3%) showed SFcr values <0. SFcr that correlated significantly and negatively with efferent arteriolar resistance (Re) and glomerular hydrostatic pressure (Pglo) (Re: r = −0.30, p = 0.008; Pglo: r = −0.28, p = 0.025). In multiple regression analyses, Re and Pglo were significantly and negatively associated with SFcr after adjustment for other confounders. Conclusions: These findings suggest that tubular reabsorption of Cr can occur in some cases. Intrarenal glomerular hemodynamic burden may be related to tubular creatinine reabsorption, which possibly leads to lower Ccr values.